Social Capital, Health, and Francophone Minorities - Bouchard, Louise (Can J Public Health, 2006)
The goal of this article is to outline the analytical perspectives of the concept of social capital regarding health and health management. Social capital, as defined in terms of social networks and resources, has a positive impact on a number of areas, notably the health, well-being, and social and economic development of communities. It is also a useful tool for implementing social policy, especially for marginal populations, the elderly, social assistance payments, etc. An action strategy based on the support and development of networks is the key to achieving the social development, health, and well-being of populations. The social ties promoted by these networks provide people with social, cognitive, and emotional support. This has a direct impact on their self-esteem and sense of personal achievement. They also facilitate access to social resources, including social advancement opportunities. In this paper, we examine the vitality, determinants of health, and health management of Canada’s minority Francophone communities. ELECTRONIC SUPPLEMENTARY MATERIAL: Supplementary material is available for this article at 10.1007/BF03405368 and is accessible for authorized users.